Psychological drivers of Sustainability: Examining happiness and progress toward the SDGs - Yimei Man (Cleaner Production Letters, 2025)
Sustainability is a global imperative, yet the role of human psychology in shaping progress toward sustainable development remains underexplored. This study investigates the relationship between psychological factors – specifically life satisfaction and happiness – and the achievement of Sustainable Development Goals (SDGs). Utilising data from the World Happiness Index (WHI) and the 17 SDGs across 131 countries from 2011 to 2021, this research explores how subjective well-being influences national progress toward sustainable development. Using Fully Modified Ordinary Least Squares to address serial correlation and endogeneity, the analysis reveals that higher levels of life satisfaction and happiness are positively associated with progress on socioeconomic sustainable goals, but are insignificantly or negatively correlated with environmental sustainable goals. These findings highlight the dual role of human psychology in advancing sustainable development: while fostering societal well-being drives progress on certain goals, it can pose challenges for environmental objectives. Policymakers should incorporate psychological dimensions into sustainability frameworks to better align human motivations with the achievement of sustainable goals, fostering an approach that balances well-being with environmental stewardship.